Sarcopenia prevalence and factors associated with sarcopenia in older people living in a nursing home in Ankara Turkey. Issue 8 (5th August 2015) - Yalcin, Ahmet; Aras, Sevgi; Atmis, Volkan; Cengiz, Ozlem Karaarslan; Varli, Murat; Cinar, Esat; Atli, Teslime
Abstract : Aim: Sarcopenia is prevalent in older people, and is related to survival and disability. There are no data on sarcopenia evaluated according to European Working Group on Sarcopenia in Older People criteria for nursing home residents in Turkey. We aimed to evaluate the prevalence of sarcopenia according to European Working Group on Sarcopenia in Older People criteria and associated factors with sarcopenia among nursing home residents in Turkey. Methods: The study cohort consisted of individuals aged over 65 years and living in the Seyranbağları Nursing Home and Rehabilitation Center in Ankara, Turkey. Besides demographic and medical data, Mini‐Mental State Examination, activities of daily living, Mini‐Nutritional Assessment, body mass index, calf circumference, gait speed and handgrip strength were also investigated. Muscle mass was evaluated by bioelectrical impedance analysis. Sarcopenia was diagnosed according to European Working Group on Sarcopenia in Older People criteria. Results: A total of 141 older individuals were evaluated. Sarcopenia was found in 29% ( n  = 41) of the participants. Participants with sarcopenia were older and had low scores for activities of daily living, low body mass index, greater cognitive dysfunction, high malnutrition risk and low calf circumference. Body mass index and calf circumference were found to be associated with sarcopenia in multivariate logistic regression analysis. Conclusions: Almost one‐third of older nursing home residents were diagnosed with sarcopenia according to European Working Group on Sarcopenia in Older People criteria in this study in Turkey. Calf circumference and body mass index were associated with increased risk of sarcopenia among nursing home residents. This is the first study evaluating sarcopenia using European Working Group on Sarcopenia in Older People criteria in Turkey.Geriatr Gerontol Int 2016; 16: 903–910.